From loosely coupled systems to collaborative business ecosystems - Stephan E. Göthlich (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2003)
Cooperations among firms as well as enterprise networks - albeit not a new phenomenon - gain attention both in science and practice since state of the art technologies such as internet and new information- and communication-media open new dimensions of its design. Network structures and concepts of collaboration are perceived as effective means to cope with the challenges of 21st century business life that is characterized as globalized and increasingly volatile, competitive and unstable. Numerous theoretical approaches to view interorganizational relationships exist. They range from the examination of pure market relationships via strategie alliances to complex and loosely coupled systems. Several economic theories such as institutional economics to name but one aspire to explain aspects of cooperations. These are generally focused on singular aspects only and therefore allow only restricted conclusions for strategy. In this article a holistic model for the understanding of business environments is derived from biological ecosystems. On this foundation three generic business strategies are outlined as well as hypotheses on the objectives that are likely to yield stability and sustainable success in the markets of the like described above. In this context the concept of resilience seems to play an important role. Finally first anecdotal evidence is provided where traditional theories fail to explain occurrences of today's business life but where the business ecosystem model indeed offers plausible insights.
Keywords: 650; Unternehmenskooperation; Unternehmensnetzwerk; Umwelt; Theorie